KAJIAN KAPASITAS RUANG TUNGGU KEBERANGKATAN DOMESTIK PADA JAM SIBUK DI BANDAR UDARA INTERNASIONAL MINANGKABAU – PADANG - Kadek Agus Agastia Paramartha; Yenni Arnas; Indria Sari Purwaningrum (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
Along with the increasing number of service users of airport service providers are required to be able to maintain the quality of flight service, one of which is the service on increasing the capacity of the waiting room at the airport. It may lead to complaints from service users. The desired service is the creation of a waiting room capacity capable of accommodating the number of passengers departing during peak hours, where according to the applicable provisions, that the area of passengers during peak hours is 1.4 m2 Domestic) and 1.7 m2 (International) if the area of waiting room in The airport meets the area of the room, it can overcome the accumulation of the number of passengers during peak hours and can improve the service quality of service users in terms of service in the waiting room in accordance with the desired needs